2021
DOI: 10.1002/pca.3033
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis of dandelions from different geographical regions in China

Abstract: Introduction: Dandelion (Taraxacum mongolicum Hand.-Mazz.) is a perennial herb with diverse pharmacological effects. The development and utilization of dandelion have attracted much attention.Objectives: Our aims were to provide a reference basis for the identification of the origin of dandelions and to study the influence of their origin on their quality. MethodsHigh-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry was used to analyze metabolites from dandelions from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Environmental stress generates an enhancement of these metabolic pathways, causing elevated metabolite concentrations, so the samples from Gansu has higher quality relatly. This study not only analyze the metabolite differences between samples, but also conducted the exploration of metabolic pathways to speculate on the association between climate factors and metabolites, which can be used to guide production [ 63 ].…”
Section: The Application Of Plant Metabolomics In Quality Evaluation ...mentioning
confidence: 99%
“…Environmental stress generates an enhancement of these metabolic pathways, causing elevated metabolite concentrations, so the samples from Gansu has higher quality relatly. This study not only analyze the metabolite differences between samples, but also conducted the exploration of metabolic pathways to speculate on the association between climate factors and metabolites, which can be used to guide production [ 63 ].…”
Section: The Application Of Plant Metabolomics In Quality Evaluation ...mentioning
confidence: 99%
“…However, the geographical origin of herbal medicines has been indicated as a crucial factor influencing the quality and potential treatment efficacy of the medicinal materials, which could be attributed to the variations in the environmental conditions and genetic reasons [85]. Zhang et al [86] confirmed that there were obvious differences in chemical components of dandelions from four different geographical regions by metabolomics analysis, especially in phenolic compounds. To ensure the health benefits and clinical effectiveness of herbal medicine to consumers, it is necessary to develop strategies for the recognition of geographic origin crud drugs.…”
Section: Geographical Origin Discrimination Strategy For Medicinal Pl...mentioning
confidence: 99%
“…At present, GNPS is widely used in metabolomics, the identification of chemical components of herbal medicines and discovery of new compounds [ 20 , 21 , 22 , 23 ]. Additionally, multivariate statistical analysis, including principal component analysis (PCA) and orthogonal partial least-squares-discriminant analysis (OPLS-DA), provides a credible way to evaluate the holistic variation, and identify chemical markers in distinguishing origin, different parts and processing methods of herbs [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%